Copy number, linkage disequilibrium and disease association in the FCGR locus. - Niederer, H; Willcocks, L; Rayner, T; Yang, W; Lau, Y; Williams, T; Scott, J; Urban, B; Peshu, N; Dunstan, S; Hien, T; Phu, N; et al. (2010)
The response of a leukocyte to immune complexes (ICs) is modulated by receptors for the Fc region of IgG (FcgammaRs), and alterations in their affinity or function have been associated with risk of autoimmune diseases, including systemic lupus erythematosus (SLE). The low-affinity FcgammaR genomic locus is complex, containing regions of copy number variation (CNV) which can alter receptor expression and leukocyte responses to IgG. Combined paralogue ratio tests (PRTs) were used to distinguish three intervals within the FCGR locus which undergo CNV, and to determine FCGR gene copy number (CN). There were significant differences in FCGR3B and FCGR3A CNV profiles between Caucasian, East Asian and Kenyan populations. A previously noted association of low FCGR3B CN with SLE in Caucasians was supported [OR = 1.57 (1.08-2.27), P = 0.018], and replicated in Chinese [OR = 1.65 (1.25-2.18), P = 4 x 10(-4)]. There was no association of FCGR3B CNV with vasculitis, nor with malarial or bacterial infection. Linkage disequilibrium (LD) between multi-allelic FCGR3B CNV and SLE-associated SNPs in the FCGR locus was defined for the first time. Despite LD between FCGR3B CNV and a variant in FcgammaRIIB (I232T) which abolishes inhibitory function, both reduced CN of FCGR3B and homozygosity of the FcgammaRIIB-232T allele were individually strongly associated with SLE risk. Thus CN of FCGR3B, which controls IC responses and uptake by neutrophils, and variations in FCGR2B, which controls factors such as antibody production and macrophage activation, are important in SLE pathogenesis. Further interpretations of contributions to pathogenesis by FcgammaRs must be made in the context of LD involving CNV regions.